Peran Akuntansi Manajemen dalam Pengambilan Keputusan Strategis pada Perusahaan Manufaktur (Jurnal Kendali Akuntansi, 2025)
This study examines the role of management accounting in supporting strategic decision-making in manufacturing companies in Indonesia. With a literature study approach and Systematic Literature Review (SLR), this study analyzes various secondary sources from 2020 to 2025. The results of the study indicate that management accounting functions as the main tool in planning, cost control, performance evaluation, and strategic decision-making. The information generated such as cost data, budgets, and performance reports greatly assists management in choosing effective and responsive strategic alternatives to market dynamics. Case studies of several large manufacturing companies show that the implementation of a good management accounting system can improve operational efficiency, optimize resource allocation, and reduce the risk of failure in decision-making. Management accounting also plays a role in supporting investment and product development to maintain competitiveness in the global market. In conclusion, management accounting is a crucial element that strengthens strategic decision-making, so that manufacturing companies can grow and be sustainable in a competitive business environment.